Mechanistic study on the corrosion behaviour of Zinc and Zinc-Calcium alloys designed for enhanced metallic coatings in the presence of chloride and phosphate ions. (1st April 2023) - Malla, A.D.; Sullivan, J.H.; Penney, D.J.; Dunlop, T.; Barker, P.
Abstract: Additions of 1 wt.% Ca were made to Zn (Zn-1Ca) to generate favourable chemical conditions during corrosion for enhanced performance of phosphate inhibitors. Zn-1Ca displayed a reduced corrosion rate in 0.17 M NaCl measured using the Scanning Vibrating Electrode Technique and polarisation. In-situ timelapse microscopy and SEM-EDS demonstrated that intermetallic CaZn13 preferentially corroded releasing Ca 2+ that increased corrosion product precipitation, cathodically deactivating the system. 1 × 10 −3 mol dm −3 phosphate additions to 0.17 M NaCl decreased the corrosion rate of Zn and Zn-1Ca. Inhibition was greater for Zn-1Ca where uniform precipitation of mixed metal phosphates produced anodic and cathodic inhibition. Highlights: Addition of 1 wt.% Ca to Zn (Zn-1Ca) reduced its corrosion rate compared to Zn. Distributed CaZn13 phases are preferentially corroded producing Ca 2+ ions. Zn-1Ca had increased corrosion products, cathodically deactivating the system. Additions of phosphate ions inhibit the corrosion of both Zn and Zn-1Ca. Inhibition is increased for Zn-1Ca due to precipitation of mixed metal phosphates.